Patient self-reported concerns in inflammatory bowel diseases: A gender-specific subjective quality-of-life indicator. - Valérie Pittet; Carla Vaucher; Florian Froehlich; Bernard Burnand; Pierre Michetti; Michel H Maillard; Swiss IBD Cohort Study Group (PLoS ONE)
Background Patient-reported disease perceptions are important components to be considered within a holistic model of quality of care. Gender may have an influence on these perceptions. We aimed to explore gender-specific concerns of patients included in a national bilingual inflammatory bowel disease cohort. Methods Following a qualitative study, we built a questionnaire comprising 37 items of concern. Answers were collected on a visual analog scale ranging from 0 to 100. Principal axis factor analysis was used to explore concern domains. Linear multiple regressions were conducted to assess associations with patient characteristics. Results Of 1102 patients who replied to the survey, 54% were female and 54% had Crohn's disease. We identified six domains of concern: socialization and stigmatization, disease-related constraints and uncertainty, symptoms and their impact on body and mind, loss of body control (including sexuality), disease transmission, and long-term impact of the disease. Cancer concerns were among the highest scored by all patients (median 61.8). Severity of symptoms was the only factor associated with concerns, unrelated to dimension and gender (p<0.015). In women, being >40 years decreased disease-related constraints and uncertainty concerns, and being at home or unemployed increased them. Treatments were associated with increased socialization and stigmatization and with increased disease-related constraints and uncertainty concerns in men. Overall, psychosomatic characteristics were highly associated with concerns for both men and women. Depending on the concern dimensions, increased levels of concern were associated with the highest signs of anxiety in women or depression in men, as well as lower health-related quality of life in men. Conclusions Patients have numerous concerns related to their illness that need to be reassessed regularly. Concerns differ between men and women, suggesting that information and communication about the disease should take gender differences and subjective perceptions of quality of life into consideration.